Altered Glymphatic System in Middle-Aged cART-Treated Patients With HIV: A Diffusion Tensor Imaging Study - Nguchu, Benedictor Alexander; Zhao, Jing; Wang, Yanming; de Dieu Uwisengeyimana, Jean; Wang, Xiaoxiao; Qiu, Bensheng; Li, Hongjun (Frontiers in Neurology, 2022)
Objective: The brain relies on the glymphatic system to clear metabolic wastes and maintain brain homeostasis to fulfill its functions better. Yet, the complexity of the glymphatic flow and clearance and its changes in HIV infection and its role in neurocognitive dysfunction remain poorly understood. This study aims to explore the impact of HIV and combination antiretroviral therapy (cART) on the glymphatic system and establish a potential biomarker of HIV-associated neurocognitive disorders (HAND). Methods Here, we examined the glymphatic profiles of middle-aged virosuppressed patients with HIV (n = 27) receiving cART over 1–6 years and healthy controls (n = 28) along the perivascular space (PVS) using diffusion tensor image analysis along the perivascular space (ALPS) with guided and unguided approaches. We later combined data from these analyses to investigate MRI glymphatic correlates of cognitive impairment and other clinical tests of HIV (CD4+ T-cell counts and CD4+/CD8+ ratio). Results We found that glymphatic function as measured by the ALPS index increased significantly in the right and left PVSs of patients with HIV having cART. On antiretroviral therapy, a changing pattern in glymphatic clearance function in patients with HIV having cART correlated with attention and working memory. Duration on cART was also associated with cognitive performances of abstract and executive function and learning and memory. Conclusion These findings provide MRI evidence of the presence of HIV-induced changes in the glymphatic flow and clearance, which might underlie cognitive impairment among patients with HIV having cART. An increase in the glymphatic activity might reflect a compensatory mechanism to regulate microenvironment homeostasis compromised by HIV. This compensation might be necessary to maintain the proper functioning of the brain while coping with HIV pathology. These findings also shed light on the clinical importance of evaluating glymphatic function based on the ALPS index and suggest that improving the glymphatic system may serve as an alternative therapeutic strategy for HAND.